A Legal Review of the Protection of Civil Servants Regarding the Annulment of Dismissal Without Honor Decisions by the Administrative Court: Tinjauan Yuridis Perlindungan Pegawai Negeri Sipil Atas Pembatalan Keputusan Pemberhentian Tidak Dengan Hormat Oleh Pengadilan Tata Usaha Negara - Safira Dina Fakhirah; Bayu Prasetyo; Elviandri Elviandri (Indonesian Journal of Law and Economics Review, 2026)
General Background Civil servants hold a central position in public administration, yet dishonourable discharge decisions must comply with legality, justice, and good governance principles. Specific Background This study examines the annulment of State Administrative Decisions concerning dishonourable dismissal of Civil Servants by the State Administrative Court in Decisions Number 45/G/2018/PTUN.SMD and 65/G/2019/PTUN.SMD. Knowledge Gap Previous studies have largely discussed the normative basis of civil servant dismissal, while limited attention has been given to legal protection, legal certainty, justice, and the nonretroactivity principle in annulled dismissal decisions. Aims The study aims to analyze the forms of legal protection for Civil Servants following the annulment of dishonourable dismissal decisions and to assess whether such annulment reflects legal certainty and justice within administrative law. Results The findings show that both dismissal decisions contained procedural and substantive defects because they were issued without careful consideration of the plaintiffs’ prior administrative status, including reinstatement, continued employment, salary recognition, and promotion. Novelty This study specifically links the annulment of dishonourable dismissal decisions with preventive and repressive legal protection, the General Principles of Good Governance, and the prohibition of retroactive administrative decisions. Implications The findings underline the need for clearer technical guidelines, careful administrative examination, and consistent personnel governance to prevent legally defective decisions and future employment disputes. Highlights: KTUN PTDH contained procedural and substantive defects in both examined cases. AAUPB requires careful, proportional, and consistent decision-making by personnel authorities. Prior reinstatement, continued employment, and promotion must be considered before PTDH issuance. Keywords:  Legal Protection, State Administrative Decisions, Dishonorable Dismissa, State Administrative Court, Civil Servants.